(untitled) (Вестник КазНУ. Серия Востоковедения, 2017)
The article shows the total investment activity in the mining industry of the Republic of Kazakhstan, and identifies the presence of the Chinese side in this financial activity. The mining and metallurgical sector is one of the most competitive and dynamically developing industries of Kazakhstan. «Investment for subsoil resources» is the formula of the Chinese investments, i.e. instead of the granted credits China requires the access to oil, gas, copper, gold and other deposits. Certainly, the Republic of Kazakhstan takes a special place in China’s range of interest. It is associated with huge inner market of the region, high purchasing power in compare to other Central Asian regions, and, as a most important, with vast range of mineral resources, especially, of hydrocarbons.